2017
DOI: 10.1177/1060028017721241
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Pharmacist-Managed Anticoagulation Therapy in Long-Term Ambulatory Settings: A Systematic Review

Abstract: Compared with routine care, pharmacist-managed outpatient-based anticoagulation services attained better quality of anticoagulation control, lower bleeding and thromboembolic events, and resulted in lower health care utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 47 publications
5
54
1
1
Order By: Relevance
“…Adhering to this higher threshold of quality in anticoagulation therapy management may be possible due to the skills and specialized training of pharmacists in anticoagulation therapy. 21 Our findings are also supported by previous studies which reported that anticoagulation management services improve the quality of care provided to patients, 8 and that pharmacist-specific models of anticoagulation service result in better patient outcomes compared with routine medical care. 6,9,13,16,[21][22][23][24][25] An acknowledged limitation of our study, however, is that with the nature of a retrospective observational cohort study, we were not able to randomly assign patients to PMAC or NMAC groups.…”
Section: Discussionsupporting
confidence: 86%
“…Adhering to this higher threshold of quality in anticoagulation therapy management may be possible due to the skills and specialized training of pharmacists in anticoagulation therapy. 21 Our findings are also supported by previous studies which reported that anticoagulation management services improve the quality of care provided to patients, 8 and that pharmacist-specific models of anticoagulation service result in better patient outcomes compared with routine medical care. 6,9,13,16,[21][22][23][24][25] An acknowledged limitation of our study, however, is that with the nature of a retrospective observational cohort study, we were not able to randomly assign patients to PMAC or NMAC groups.…”
Section: Discussionsupporting
confidence: 86%
“…Our patient cohort had a slightly lower TTR (63% vs 67%) than that reported in a recent NZ study in which patients were managed by their general practitioner using decision‐support software . More significantly, where this software has been combined with pharmacist‐led warfarin management in NZ and elsewhere, this has led to higher TTR (>70%) than in those patients managed by general practitioners . Although confounders may account for some of these discrepancies, the higher TTR probably reflect better adherence to decision‐support recommendations .…”
Section: Discussioncontrasting
confidence: 62%
“…2 More significantly, where this software has been combined with pharmacist-led warfarin management in NZ and elsewhere, this has led to higher TTR (>70%) than in those patients managed by general practitioners. 17 Although confounders may account for some of these discrepancies, the higher TTR probably reflect better adherence to decision-support recommendations. 2 These studies suggest that anticoagulant control in our regions could be improved by improving education for general practitioners, widening access to decisionmanagement software, and encouraging pharmacist-led monitoring.…”
Section: Inr Monitoring In Auckland and Northlandmentioning
confidence: 99%
“…The impact of outpatient clinical pharmacy services has been well supported throughout a variety of disease states including asthma, anticoagulation, pain, heart failure, geriatrics, diabetes, and smoking cessation. Pharmacists in these settings have shown improvements in adherence, better management of adverse effects, and overall cost reduction …”
Section: Introductionmentioning
confidence: 99%